A global study of poverty and livestock - Thornton, Philip K. (International Livestock Research Institute, 2002)
This study which is commissioned by DFID (Department for International Development) in 2001 is conducted to produce sets of maps locating significant populations of poor livestock keepers in the world, and to assess in very broad terms how these populations are likely to change over the next three to five decades. The outputs were to include maps illustrating the global distribution of poor livestock keepers, and the project was to make use of existing data and spatial data layers, together with information from the literature and the opinion of appropriate experts. Data inputs for the production of global (Africa, Asia, Latin America) and regional (Kenya, Tanzania, Uganda) poverty maps are presented. Global livestock production systems and density of poor livestock keepers by farming systems are indicated the on world map.